ANALYSIS OF RISK FACTORS FOR DEATH IN PATIENTS WITH COVID-19 IN 2021 AT UNIVERSITAS AIRLANGGA HOSPITAL: Analisis Faktor Risiko Kematian Pada Penderita COVID-19 Tahun 2021 di Rumah Sakit Universitas Airlangga - Ayunda Solehan, Zahra; Atikasari, Fitri; Dwi Artanti, Kurnia; Asta Wulaningrum, Prastuti; Is Effendi, Wiwin; Yi Li, Chung (Universitas Airlangga, 2024)
Background: Coronavirus Disease 2019 (COVID-19) is an infectious disease caused by SARS-CoV2, first detected in China in 2019. This disease causes respiratory infections and significantly impacts global health. Purpose: This study aims to analyze the risk factors for mortality in COVID-19 patients at Universitas Airlangga Hospital in 2021. Methods: This observational analytical study uses a case-control design, including 168 samples with 64 cases and 64 controls. Secondary data from patient medical records at Universitas Airlangga Hospital, including age, gender, education, comorbidities, oxygen saturation, and length of stay. Chi-square tests analyzed the data with a 95% confidence level (α=5%). Results: The analysis revealed significant associations between COVID-19 mortality and several factors. Age (p=0.01; OR=3.24; 95%CI=1.57-6.65), gender (p=0.01; OR=2.2; 95%CI=1.17-4.02), education (p=0.00; OR=2.40; 95%CI=1.11-5.40), comorbidities (p=0.08; OR=2.50; 95%CI=1.26-4.91), and oxygen saturation (p=0.00; OR=5.40; 95%CI=117.10-2490.06) were significantly associated with COVID-19 mortality. Oxygen saturation was the most influential factor (p=0.00; OR=901.73; 95%CI=120.75-6733.48) associated with mortality. Conclusion: Age, gender, education, comorbidities, and oxygen saturation significantly affect Covid-19 mortality rates. This study highlights the importance of monitoring and managing these risk factors in managing COVID-19 at Universitas Airlangga Hospital.